The Frequency of Prescription of Immediate-Release Nifedipine for Elderly Patients in Germany: Utilization Analysis of a Substance on the PRISCUS List of Potentially Inappropriate Medications - Schubert, Ingrid (Deutscher Arzte Verlag, 2012)
BACKGROUND: Immediate-release nifedipine is on the PRISCUS list of drugs that should not be given to elderly patients. We studied the use of this calcium-channel blocker under real-life conditions. METHODS: In 2009, we carried out a cross-sectional study based on the Statutory Health Insurance Sample AOK Hesse/KV Hesse with a sample size of 260 672 insurees. We used an anatomic-therapeutic-chemical classification (C08) to identify prescriptions for calcium-channel blockers. We determined from brand names and dosage forms whether nifedipine was prescribed in an immediate-release or sustained-release formulation. RESULTS: Among insurees over age 65, the prevalence of treatment with immediate-release and sustained-release nifedipine was 0.9% and 1.0%, respectively. Immediate-release nifedipine was usually (75%) given in a single administration. 46% of patients receiving immediate-release nifedipine also received another calcium-channel blocker. Patients who received immediate-release nifedipine tended to take more cardiovascular drugs than those who received sustained-release nifedipine (6 or more cardiovascular drugs were taken by 30% and 16%, respectively). Among all medical diagnoses related to hypertension, two were significantly more common among patients taking immediate-release nifedipine than among those taking sustained-release nifedipine: hypertensive crisis (OR 4.26, 95% CI 2.45–7.40) and hypertensive heart disease (OR 1.82, 95% CI 1.04–3.19). CONCLUSION: Our analysis demonstrates that immediate-release nifedipine is being prescribed to elderly patients in Germany, albeit mostly in a single administration. In view of the risks and the availability of alternative drugs, stricter adherence to the PRISCUS recommendations in this case should be stressed in continuing medical education.